Respuesta :
Answer:
see explanation
Step-by-step explanation:
if the denominator of a rational expression is zero then the expression will be undefined.
the numerator is the part of the rational expression that makes it zero.
solve the numerators in each to find values of x
1
[tex]\frac{x+6}{x-4}[/tex]
x + 6 = 0 ( subtract 6 from both sides )
x = - 6 ← value that makes expression equal to zero
2
[tex]\frac{(x+4)(x-2)}{x+6}[/tex]
(x + 4)(x - 2) = 0
equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
x - 2 = 0 ⇒ x = 2
x = - 4 and x = 2 make the expression equal to zero
3
[tex]\frac{2x+10}{3x-12}[/tex]
2x + 10 = 0 ( subtract 10 from both sides )
2x = - 10 ( divide both sides by 2 )
x = - 5 ← value that makes expression equal to zero
Answer:
1) x = -6
2) x = -4 and x = 2
3) x = -5
Step-by-step explanation:
A rational expression is undefined when the denominator equals zero.
A rational expression equals zero when the numerator equals zero.
Question 1
Given rational expression:
[tex]\dfrac{x+6}{x-4}[/tex]
Set the numerator to zero and solve for x:
[tex]\implies x+6=0[/tex]
[tex]\implies x=-6[/tex]
Question 2
Given rational expression:
[tex]\dfrac{(x+4)(x-2)}{x+6}[/tex]
Set the numerator to zero:
[tex]\implies (x+4)(x-2)=0[/tex]
Apply the zero-product property and solve for x:
[tex]\implies x+4=0 \implies x=-4[/tex]
[tex]\implies x-2=0 \implies x=2[/tex]
Question 3
Given rational expression:
[tex]\dfrac{2x+10}{3x-12}[/tex]
Factor the numerator and denominator:
[tex]\dfrac{2(x+5)}{3(x-4)}[/tex]
Set the numerator to zero and solve for x:
[tex]\implies 2(x+5)=0[/tex]
[tex]\implies x+5=0[/tex]
[tex]\implies x=-5[/tex]